Investigando a reconstrução do estilo de ação do professor em eventos de leitura - Carvalho, Arli Pires de (2014)
The main objective of this research is to investigate the actions of the teacher researcherin situations of interaction with a group of boys, in literacy events, as well as analyze and discuss how students and also teachers construct meanings and develop argumentation skills, reflection, collective reasoning, using the technique of Group Think-Aloud (GTA) (ZANOTTO, in press) or Verbal Protocol. In this sense, I seek grants for working with teachers in a group coordinated by me in a state school.The technique of GTA is inserted in Applied Linguistics Area. It is researched in Brazil by GEIM Study Group of Indeterminacy and Metaphor (ZANOTTO, 1995, 1998, 2008; ZANOTTO and PALMA, 2008, 2013), under the coordination of ZANOTTO and allowed the generation of research data in five experiences of reading, which were recorded, transcribed and analyzed in order to observe how students and teacher researcher constructed meanings during reading activity. In this sense, the focus is on the following research questions: (1) Howpractice of reading PAG may contribute about development of students asprotagonists of the read act? (2) How, from the analysis and discussion of the teacher researcher actions in literacy events PAG, is it possible to build a new discourse to interact with the students?The results showed ushow the interaction between teacher and students occurred;also showed how participants reasoned, constructed arguments, inferences, understanding, and how the teacher researcher orchestrated the voices of students through the literacy GTApractices, which enabled the group to respect the subjectivity of each participant, giving them voice. The analysis of theteacher researcher actions showed us the need to change from the traditional approach in the classroom, as well as mediating actions of reading as social and cultural practicesfrom the perspective of Group Think-Aloud